Hubungan antara Environmental Performance Tahun Sebelumnya dengan Economic Performance Tahun Berjalan (Studi pada perusahaan tambang yang mengikuti program PROPER dan terdaftar di IDX) - Runtu, Treesje; Naukoko, Princilvanno Andreas (Universitas Sam Ratulangi, 2014)
The purpose of this research is to know is there any significant correlation between last year environmental performance and presents economic performance. This research use 6 companies who are participant of PROPER 2011-2012, and listed in IDX. The methods of this research is using bivariate correlations with significant testing as the hypothesis test. The results of hypothesis testing shows that correlation between last year environmental performance and present economic performance are very weak, positively and not significant.